2014
DOI: 10.3906/vet-1407-29
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the immunology and uterine microbiology of healthy cows and cows that develop uterine disease

Abstract: Uterine diseases are highly prevalent in dairy cows. Causes of uterine diseases are multifactorial. There is good evidence for the susceptibility of the host and for the role of pathogenic bacteria, and less evidence for the effect of the environment. Uterine and leukocyte immune response is impaired early postpartum in cows that develop uterine disease. The decrease in immune function is associated with a decrease in calcium postpartum and an increase in NEFA and BHBA. Both endometrial cells and granulosal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…may increase the bacterial load and the challenge to the immune system. Trauma to the vulva and vagina may also indicate trauma to the uterus, which may compromise the uterine innate immunity capabilities such as endometrial physical barriers, pathogen recognition, recruitment of professional phagocytes, and production of antimicrobial peptides (Sheldon et al, 2009;Galvão and Santos, 2014;Sheldon, 2014). Gilbert et al (2007) reported that proportion of PMN in the uterus on the day of calving was negatively correlated with uterine bacterial contamination on the day of calving and with PMN proportion (cytological endometritis) at 49 DIM.…”
Section: Variablementioning
confidence: 99%
“…may increase the bacterial load and the challenge to the immune system. Trauma to the vulva and vagina may also indicate trauma to the uterus, which may compromise the uterine innate immunity capabilities such as endometrial physical barriers, pathogen recognition, recruitment of professional phagocytes, and production of antimicrobial peptides (Sheldon et al, 2009;Galvão and Santos, 2014;Sheldon, 2014). Gilbert et al (2007) reported that proportion of PMN in the uterus on the day of calving was negatively correlated with uterine bacterial contamination on the day of calving and with PMN proportion (cytological endometritis) at 49 DIM.…”
Section: Variablementioning
confidence: 99%
“…Innate immunity is the most important defense system of the bovine uterus and mammary gland, and the neutrophil is the main cell type involved in innate immunity in those organs (Hussain, 1989;Paape et al, 2003). However, during the transition into lactation, dairy cows experience a reduction in leukocyte function, including a reduction in neutrophil phagocytosis and killing capacity, which is believed to be a predisposing factor to infectious diseases such as metritis and mastitis (Goff and Horst, 1997;Hammon et al, 2006;Galvão and Santos, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The same author suggested that, at calving, distinct levels of calcium between groups should be considered as relevant for the occurrence of uterine disorders. This is because calcium has a fundamental role in muscle contraction and immune responses (GOFF, 2008), thus being important for the activation and chemotaxis of defense cells (GOFF; HORST, 1997;GALVÃO;.…”
Section: Discussionmentioning
confidence: 99%